Systematic review of neuroendocrine carcinomas of the oropharynx. Issue 7 (18th April 2022) - Froehlich, Michael H.; Shih, Michael C.; Shehee, Lindsey; Kompelli, Anvesh R.; Aylward, Alana; Nguyen, Shaun A.; Kaczmar, John M.; Nathan, Cherie Ann; Day, Terry; Neskey, David M.
Abstract: Data describing features and management of oropharyngeal neuroendocrine carcinomas (NEC) remain sparse. A systematic review was performed. Patients were stratified by treatment modality and examined for disease progression and survival outcomes. Ninety‐four patients from 50 publications were included. Average age at diagnosis was 59.7 years (range 14–83). 73.4% were male. Most studies did not document HPV status. Forty patients (85.1%) were p16 positive, and 34 (85.0%) were HPV‐ISH positive. Overall survival was 75.4% at 1 year, and 40.0% at 2 years. Of patients with locoregional disease, 33.8% developed distant metastasis. 12.5% of patients developed locoregional recurrence. Patients who developed distant metastases had worse overall survival ( p  = 0.0004). No significant difference was found between treatment modalities. Human papilloma virus may be associated with oropharyngeal NEC. Current treatments provide locoregional control, but distant metastases are common and confer low overall survival.